Penyuluhan dan Pelatihan Strategi Pemasaran dalam Mendukung Kegiatan Kewirausahaan pada Karangtaruna di Desa Kunir, Kutoarjo, Jawa Tengah - Elwisam Elwisam; Resti Hardini; Molina Molina; Melati Melati; Nayudha Shandy; Priono Hasiholan Purba (LPMP Imperium, 2023)
Marketing strategies are needed in carrying out entrepreneurial activities for competitive advantage. Marketing strategy is a state of mind that will be used to achieve marketing goals, which can be in the form of specific strategies for target markets, positioning, marketing mix mix and the amount of marketing expenditure. Marketing strategies can be applied to entrepreneurial activities as a weapon of competitive advantage with the aim of earning profits. This is necessary by encouraging human resources to carry out entrepreneurial activities to form independent people who are expected to also contribute to regional economic development. The Karang Taruna of Kunir village, Kutoarjo, Central Java with village youth members has a very low level of activity and productivity. Marketing strategy outreach and training activities in supporting entrepreneurial activities have the aim of providing insight accompanied by training to create entrepreneurial motivation by implementing appropriate marketing strategies. Before the implementation of PKM, only 20% of participants had an interest in entrepreneurship by implementing appropriate marketing strategies. After counseling and training, 85% of the participants had the motivation to become entrepreneurs through implementing appropriate marketing strategies. This illustrates the success of community service activities in providing motivation, discourse and training to the Kunir village youth organization in forming independent and productive people who are expected to contribute to the development of the village economy.